The “Bogus” Refugee: Roma Asylum Claimants and Discourses of Fraud in Canada’s Bill C-31 - Diop, Petra Molnar (Refuge: Canada’s Journal on Refugees, 2014)
The passage of Bill C-31 into Canadian law in June 2012 is part of a discourse created around refugees by the current Government of Canada. Refugees are divided into “good and proper” refugees who live in camps abroad, and the “ fraudulent and bogus” refugees who claim asylum at the Canadian border. The new act, Bill C-31 or Protecting Canada’s Immigration System Act, is analyzed with respect to changes that will result in the systematic exclusion of certain groups of asylum seekers from Canada, based on these discourses of “bogus” and “fraud,” even though these groups may include genuine refugees. Drawing on the case of Czech Roma refugee claimants who come to Canada from Europe, this article shows how the Roma come to stand for the perfect “bogus” refugee — a person who wants to cheat the benevolent Canadian system without having grounds for a successful refugee status application. A critical look at the legislation provides new insights into the relations between governmentality and the regimes of citizenship, with the state performing its power in increasingly spectacular ways. Refugees act as the abject Other that legitimizes, legalizes, and reaffirms such state interventions.